2005
DOI: 10.1097/00001199-200509000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Residential Community Integration Programs for Adults With Brain Injury

Abstract: The considerable variability in characteristics of residential community integration programs for adults with brain injury presents significant challenges to researchers seeking to identify vital program components and to consumers attempting to compare programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…These measures have been useful in measuring occupational performance outcomes (Devitt et al, 2006). According to a nationwide telephone survey, occupational therapy staff were also involved in 69% of all home-based CI programs (Glenn, Rotman, Goldstein, & Selleck, 2005). This level of involvement was surpassed only by psychologists (85%).…”
mentioning
confidence: 99%
“…These measures have been useful in measuring occupational performance outcomes (Devitt et al, 2006). According to a nationwide telephone survey, occupational therapy staff were also involved in 69% of all home-based CI programs (Glenn, Rotman, Goldstein, & Selleck, 2005). This level of involvement was surpassed only by psychologists (85%).…”
mentioning
confidence: 99%
“…Respondents were programme directors or other staff familiar with all aspects of the programme. The methods have previously been described [1,9].…”
Section: Methodsmentioning
confidence: 99%
“…The results of the surveys of facility-based and residential programmes are reported elsewhere [1,9].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the emergence of team driven community integration rehabilitation programmes [17] and the development of a disability service field dedicated to travel instruction and training [12], minimal research has been conducted on issues related to travel training and use of public transportation for people with acquired brain injury. A thorough review of the literature revealed only three studies that explicitly evaluated travel training programmes to teach survivors of brain injury to use public transportation [11,18,19].…”
Section: Need For Travel Researchmentioning
confidence: 99%